1998
DOI: 10.1023/a:1007730730655
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The effects of sub-lethal doses of dichlorvos and formalin, antimicrobial/parasitic agents used in aquaculture, on lipid composition and metabolism of rainbow trout skin cells in primary culture were investigated. Both dichlorvos and, especially, formalin appeared to significantly inhibit Δ9 and Δ6 desaturase.Changes in the distribution of radioactivity between individual phospholipid classes was also influenced by formalin and dichlorvos, and this may be related to changes in desaturase activity. This study h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The primary aim of the present study was to determine if the deficiency in the desaturase/elongase pathway, established in C [18][19][20] elongase in TF cells (11), was identical in another marine fish cell line. The results obtained using the direct substrates for each individual contrast to turbot cells, fatty acyl Δ5 desaturation was the step with the lowest activity in the pathway biosynthesizing 20:5n-3 (or 20:4n-6) in the sea bream cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary aim of the present study was to determine if the deficiency in the desaturase/elongase pathway, established in C [18][19][20] elongase in TF cells (11), was identical in another marine fish cell line. The results obtained using the direct substrates for each individual contrast to turbot cells, fatty acyl Δ5 desaturation was the step with the lowest activity in the pathway biosynthesizing 20:5n-3 (or 20:4n-6) in the sea bream cells.…”
Section: Discussionmentioning
confidence: 99%
“…This was unexpected as desaturases in general are normally more active towards n-3 fatty acids in mammals (32,33) and fish cells (10,11,34).…”
Section: Discussionmentioning
confidence: 99%
“…[4] The effects of sublethal doses of dichlorvos on lipid composition and metabolism of rainbow trout skin cells in primary culture suggested that dichlorvos might have direct effects on fish skin that could have important consequences for fish health. [5] In air-breathing catfish Clarias batrachus exposed to lethal and sublethal concentrations of the dichlorvos cytoarchitectural changes in the oocytes were observed. [6] Clumping of the cytoplasm and karyohypertrophy have also observed.…”
Section: Introductionmentioning
confidence: 99%